PENGARUH KEDISIPLINAN GURU TERHADAP PRESTASI KERJA PADA MADRASAH IBTIDAIYAH (MI) ARROSIDIYAH DESA SUMBERAGUNG REJOTANGAN TULUNGAGUNG (Studi Kasus Kendali Mutu) - Suprihno, Suprihno (e-Journal STAI Muhammadiyah Tulungagung, 2015)
Lately Islamic School called madrasah as an institution of Islamic education get more attention and public trust in the appeal of public educational institutions, because madrasah will be able to fulfill the needs of science and religion, especially the religion of Islam. This research using âdescriptive statisticalâ methods. This method is used to analyze the data in a way to describe or portray the collected data itself to the population. The Result of this research presented in the form of tables, graphs, pie charts, pictogram, calculation mode, median, mean, calculating deciles, percentiles, calculation of data spread through the calculation of average and standard deviation, percentage calculations. The factors affecting the level of discipline of MI Arrosidiyah teachers is low teacher income, family problems, work environment problem, individual teachers, and work culture. As a follow-up study of quality control is suggested to MI Arrosidiah to Increase teacher salaries, improve harmonization of family, school Enforcement, Improved motivation and Competitive Culture.